Persepsi Orang Tua dalam Pengenalan Numerasi Secara Digital dan Konfensional Pada Anak Usia Dini di Lingkungan Keluarga - Ayuningtyas, Vidya; Mulyawan, Galuh; Syahidah, Alfina (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Early childhood is a golden age in children's development that greatly determines the quality of their lives in the future. At this stage, children experience very rapid cognitive, social, emotional, and motor growth. One important aspect in cognitive development is numeracy skills, namely the ability to understand, interpret, and use the concept of numbers and basic mathematical operations in everyday life. Early introduction to digital numeracy can help children build a foundation for logical, analytical, and problem-solving thinking. The family environment is the first and main place for children to learn various things, including the concept of digital numeracy. The role of parents as the first educators is very important in providing stimulation and early learning through daily activities. This study is a quantitative study with a descriptive approach that reveals a phenomenon/condition by describing it in numerical form. The research sample was parents who have children aged 0-6 years in Cigoong Village, Walantaka District, Serang City, totaling 26 people. The misconception questionnaire instrument uses the Guttman measurement scale by adapting the modified Kemendikbudristek. The results of the study show that parents' perceptions of the introduction of digital numeracy to early childhood are still mixed between correct understanding and various forms of misconceptions. In general, there is a positive understanding that early childhood is ready to be introduced to digital numeracy, but many parents still understand numeracy narrowly, only as a counting skill, and are often equated with formal academic activities